Consumer Perception of Agribusiness E-marketplace Opportunities in Indonesia - Kusumawati, Reni Diah; Oswari, Teddy; Yusnitasari, Tristyanti; Dutt, Himanshu (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
E-commerce for agribusiness products began to develop in Indonesia in 2015, but it is still very small in number when compared to products from other industries. E-marketplace allows farmers to reach a wider range of consumers, so that everyone who has internet access has the opportunity to be able to enjoy fresh agricultural products. The success of an e-marketplace is supported by the good performance of the web, so that consumers will feel comfortable in searching for products and making transactions. This study discusses the performance of e-marketplaces, and consumer perceptions to determine consumer purchase intentions of agricultural product e-marketplaces. The population in this study are consumers who have used the agricultural product e-marketplace. The data were obtained through a questionnaire, then a classic assumption test was carried out to determine the appropriateness of the statements used in the questionnaire and the distribution of the data used. Furthermore, the data will be analyzed using multiple linear regression. The results show that partially only the convenience of the website from the e-marketplace performance indicators that affects consumer purchase intentions of agricultural products, while other variables do not affect consumer purchase intentions of e-marketplaces that offer agricultural products. Simultaneously, the results of the study indicate that e-marketplace performance, perceived ease of use, and perceived benefits influence consumer purchase intentions in agricultural product e-marketplaces. The contribution of the influence of the independent variables to the dependent variable is 17.9%, and the rest is influenced by other variables not included in the study.